A case-control study of treatment choices made by doctors diagnosed with early breast cancer. (May 2015) - O'Connell, Rachel L.; Mohammed, Kabir; Gui, Gerald P.H.; Rusby, Jennifer E.
Abstract: Introduction: Doctors who are diagnosed with breast cancer form a small subset of women with unique insight into their disease. The aim of this study was to compare key treatment decisions in medically-qualified doctors with equivalent degree-educated, matched controls diagnosed with early breast cancer. Methods: Patients diagnosed with breast cancer between 01/01/2006 and 31/12/2011 were included and screened for occupation by 2 independent investigators. Allied health professionals with a medical background (e.g. nurses, physiotherapists) were excluded. Patient controls were matched by age, nodal status and grade. If there were more than 5 possible matches then those patients with the closest tumour size were selected. Results: 5259 of 8623 patients had signed the generic research consent form. 619 of these were either doctors, or had received tertiary level education and could form appropriate controls. After exclusions, 46 medically-qualified doctors and 230 matched control patients were included in the analysis. No statistical differences in age or tumour characteristics were identified between doctors with breast cancer and matched controls. No differences were identified between the two groups in the uptake of mastectomy, chemotherapy, immediate breast reconstruction or post-mastectomy radiotherapy. Conclusion: Medically-qualified patients diagnosed with early breast cancer are no more likely to opt for mastectomy, chemotherapy, immediate breast reconstruction or post-mastectomy radiotherapy than non-medically-qualified controls. The level of information generally provided to patients with breast cancer is adequate for a similar decision to be made by control patients with equivalent levels of education, independent of any knowledge of pathology or understanding of the medical system that medically-qualified patients may possess. Highlights: Doctors who are diagnosed with breast cancer form a small subset of women with unique insight into their disease. Anecdotally it was thought that doctors have a higher rate of mastectomy due to patient choice. This study matched doctors with breast cancer with educated, but not medically-qualified patients with breast cancer. Medically-qualified patients are no more likely to opt for mastectomy than non-medically-qualified controls.